2021
DOI: 10.1038/s41419-021-04423-y
|View full text |Cite
|
Sign up to set email alerts
|

Hippo signaling suppresses tumor cell metastasis via a Yki-Src42A positive feedback loop

Abstract: Metastasis is an important cause of death from malignant tumors. It is of great significance to explore the molecular mechanism of metastasis for the development of anti-cancer drugs. Here, we find that the Hippo pathway hampers tumor cell metastasis in vivo. Silence of hpo or its downstream wts promotes tumor cell migration in a Yki-dependent manner. Furthermore, we identify that inhibition of the Hippo pathway promotes tumor cell migration through transcriptional activating src42A, a Drosophila homolog of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…In Drosophila, the enhancement of cell migration induced by the inhibition of Scrib was shown to be mediated by Yki. 66 Furthermore, it was shown that cancer-associated phenotypes may be induced by the interaction between Scrib and Yap, which inhibits the activity of YAP. 67 In addition, apical and basal domains are physically separated by cell junction complexes.…”
Section: Key Components Of the Hippo Pathwaymentioning
confidence: 99%
“…In Drosophila, the enhancement of cell migration induced by the inhibition of Scrib was shown to be mediated by Yki. 66 Furthermore, it was shown that cancer-associated phenotypes may be induced by the interaction between Scrib and Yap, which inhibits the activity of YAP. 67 In addition, apical and basal domains are physically separated by cell junction complexes.…”
Section: Key Components Of the Hippo Pathwaymentioning
confidence: 99%
“…Loss of Scrib cell polarity regulator strongly promotes metastasis behavior of cancer cells [27]. To examine the contribution of Drp1 mitochondrial fission protein and involvement of JNK signaling to prevent metastatic behavior in Scrib abrogated cells, we tagged Ptc-Gal4 driver line with GFP.…”
Section: Resultsmentioning
confidence: 99%
“…Scrib is mislocalized to the cytoplasm of cancer cells upon loss of function mutation in Scrib complex proteins [4143]. The loss of function mutation of Scrib leads to development of neoplastic tumor [27,44]. Earlier reports from our laboratory showed larval wing tissue specific knockdown of Scrib developed neoplastic tumors with increased larval size and die as giant pupae during early stages of pupal development without differentiation [14].…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining of wing discs was carried out according to our previous protocols 61 . Briefly, third-instar larvae were dissected in PBS and fixed in 4% PFA at room temperature for 20 min, then permeabilized with PBT (PBS supplemented with 0.1% Triton X-100) for three times.…”
Section: Methodsmentioning
confidence: 99%